AB0480 A functional magnetic resonance imaging study on the psychopathology of patients with primary sjogren's syndrome and anxiety disorder. (15th June 2017) - Cui, B; Liu, Y
Abstract : Background: Sjogren syndrome (SS) is a chronic systemic autoimmune disease characterized by exocrine gland inflammation and symptoms of oral and ocular dryness. Anxiety affects as many as 50–70% of persons living with SS. While anxiety is commonly experienced, very little is known concerning the mechanisms of cognitive dysfuction in SS. Objectives: To reveal the psychopathology of patients with Sjogren's syndrome and anxiety disorder. Methods: 12 patients with pSS and anxiety disorder (SAS≥50), 11 patients with pSS, and 10 healthy controls were recruited. (1) Self-rating Anxiety Scale (SAS) were used to assess anxiety level of participations. All the subjects went through functional magnetic resonance imaging (fMRI) while listening actively to neutral words, negative words and negative words alternating with neutral ones. Results: When subjects listened to neutral words alternating with no words, prefrontal cortex and BA21 were active in patients with pSS and anxiety disorder. When subjects listened to negative words alternating with no words, patients showed increased activity in prefrontal cortex, BA21, anterior cingulate and fusiform. Furthermore, when subjects listen to negative words alternating with neutral words, patients with pSS and anxiety disorder showed more increased activity in prefrontal cortex, anterior cingulate, and caudate nucleus than that of other two groups. Conclusions: Anxiety disorder commonly exists in patients with pSS. The pathology of this psychological symptom is poorly understood, which may be one of manifestation of nervous system involvement. fMRI may provide a novel insight into the pathological process accompanying subtle psychiatric disorders commonly experienced by patients with pSS. References: Massara A, Bonazza S, Castellino G, et al. Central nervous system involvement in Sjögren's syndrome: unusual, but not unremarkable–clinical, serological characteristics and outcomes in a large cohort of Italian patients. Rheumatology (Oxford). 2010;49:1540–9. Martinez S, Cáceres C, Mataro M, et al. Is there progressive cognitive dysfunction in Sjögren Syndrome? A preliminary study. Acta Neurol Scand. 2010;122:182–8. Barbara M. Segal, Bryon A. Mueller, et al. Disruption of brain white matter microstructure in primary Sjogren's syndrome: evidence from diffusion tensor imaging. Rheumatology 2010;49:1530–1539. Liu LJ, Zhang XY, He N1, et al. Genetic variation in WDR1 is associated with gout risk and gout-related metabolic indices in the Han Chinese population. Genet Mol Res. 2016 Apr 28;15(2). doi: 10.4238/gmr.15027381. Acknowledgements: Thanks are due to Dr. Gong for assistance with the experiments and to YQ. Wang for valuable discussion.There is no financial support or other benefits from commercial sources for the work reported on in the manuscript, or no other financial interests that any of the authors may have, which could create a potential conflict of interest or the appearance of a conflict of interest with regard to the work. Disclosure of Interest: None declared